GUERILLA TACTICS, ENTREPRENEURSHIP and ANCIENT HISTORY: : The Real story behind economic marginalisation and Zama-Zamas - Pitso, Teboho (Journal of Economic Development, Environment and People, 2024)
Purpose To uncover the real story behind zama-zamas and the entrepreneurs behind their work: A Tale of Sustained Exploitation Context Limpopo villages are ensconced by 108 mining sector that contributes 72% to GDP by 2021 estimates totalling annual revenue of R237, 7 billion. Yet, poverty is almost 77% and the villages have to bear the brunt of devastation on their socio-ecological space which put them at considerable economic risk given that rehabilitation of disused mines is poorly handled at government level plus communities use the dwindling land for agricultural and pastoral purposes which means the impact of mining operations affect the livelihoods of neighbouring villages who benefit very little from mines. These are the breeding grounds for zama-zamas who are exposed to real exploitation because they have no access to the legal market. Research Methodology To uncover the real story of zama-zamas, there is a need to take a historical perspective, do Desktop research and conduct semi-structured interviews with select numbers of zama-zamas and members of the local communities where mining occurs. Findings The mining sector in Africa is ancient and begins in the 15th century when the Portuguese colonisers discovered gold on the coast of modern-day Ghana while in South Africa it started in 1867 when diamond was found on the banks of Orange River. Most zama-zamas are driven by desperation and live in chronic poverty despite the fact that this illicit mining sector is making R14 billion in the legal market. 3. Zama-zamas have to negotiate the dark side of a nefarious mineral cabal that benefits the very avar